2007
DOI: 10.1200/jop.0752001
|View full text |Cite
|
Sign up to set email alerts
|

A Bridge Between Academic and Community Radiation Oncology Treatment Planning

Abstract: Purpose: To evaluate Telesynergy (TS) as a method of interactive treatment planning between academic and community radiation oncology departments.Methods: Through a grant from the National Cancer Institute to improve cancer outcomes for underserved populations, community radiation oncologists at New Hanover Regional Medical Center (NHRMC) in Wilmington, North Carolina, partnered with those at the University of North Carolina (UNC) in Chapel Hill, North Carolina. TS suites were installed at both sites to facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Establishing clinical consultation sites at remote centers resulted in saved patient travel time, and it also provided employment opportunities for healthcare workers on the reservations and at satellite Pennsylvania hospitals. These successes were important lessons learned from the conduct of clinical trials and medical care for remote disparities communities ( 12 14 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Establishing clinical consultation sites at remote centers resulted in saved patient travel time, and it also provided employment opportunities for healthcare workers on the reservations and at satellite Pennsylvania hospitals. These successes were important lessons learned from the conduct of clinical trials and medical care for remote disparities communities ( 12 14 ).…”
Section: Resultsmentioning
confidence: 98%
“…Table 5 details how it was used. Videoconferencing facilitated communication between awardees and their mentors for treatment planning ( 12 ) and follow-up consultations at remote settings (e.g., South Dakota and Pennsylvania). It was also used among CDRP sites predominantly for training clinical research staff, tumor board conferences, research consultations, and sharing of ideas.…”
Section: Resultsmentioning
confidence: 99%
“…The system reported here has sufficiently realized our needs, though a level 1 system was the simplest in the classification of Olsen et al It should be emphasized that medical information desktop sharing reported here seems to be the first in the field of radiation oncology. There are some reports on applications of telemedicine for radiation therapy [4][5][6][7]. Suzuki et al [4] introduced a web-based remote radiation treatment planning system that allowed staff at an affiliated hospital to obtain support from a fully staffed central institution.…”
Section: Telemedicine For Radiation Therapymentioning
confidence: 99%
“…Our video conference system was not equipped with a function to make radiation therapy plans remotely; however, we did not need such a function because radiation therapy plans made by a doctor sent to an affiliated hospital could be checked in the videoconference and corrected on the spot. Maguire et al [5] reported their initial experience with a telemedicine workstation as a method for interactive intensity-modulated radiation therapy (IMRT) planning for patients with advanced head and neck squamous cell carcinoma between a university hospital and a distant regional community hospital. As an example of telemedicine applied to radiation oncology in a developing country, Agrawal et al [6] reported the establishment of a telemedicine linkage with a remote medical institute to facilitate teaching, training, and carry out collaborative clinical and translational research.…”
Section: Telemedicine For Radiation Therapymentioning
confidence: 99%
“…Keishiro Suzuki has demostrated the development of a web-based, remote radiation treatment planning system which allowed staff at an affiliated hospital to obtain support from a fully staffed central institution [ 6 ]. In a study by Maguire et al, telemedicine was shown to bridge the academic and community radiation oncology treatment planning [ 7 ]. They have demonstrated that complex radiation treatment planning review was feasible between an academic and community hospital via telesynergy network with a high level of physician satisfaction.…”
Section: Introductionmentioning
confidence: 99%